The Impact of Behavioral Symptoms of Burnout on Work Engagement of Older Employees: The Case of Slovenian Companies - Rožman, Maja; Treven, Sonja; Cingula, Marijan (Naše gospodarstvo/Our economy, 2022)
The main objective of the paper is to determine the impact of behavioral symptoms of burnout of older employees on their work engagement in large- and medium- sized companies in Slovenia. The research is based on the implementation of a factor analysis by which we wanted to reduce the large number of variables into a smaller number of factors. With those factors, we performed a simple linear regression. Based on the results, we confirmed the hypothesis that behavioral symptoms of burnout of older employees have a statistically significant negative impact on their work engagement. Well-being of employees of varying ages in the workplace is key for long-term effectiveness of companies. From this point of view, companies should apply appropriate measures to reduce burnout as well as to contribute to employees’ well-being and better workplace performance, which is reflected in work engagement of employees.